Perancangan Proses Bisnis Sistem PPDB Dengan Fokus User Experience Pada CV Mitra Global Techno (Studi Kasus TK IT AL Qolam) - Pratama, Septiano Anggun; Lamasitudju, Chairunnisa Ar; Hendra, Syaiful; Putri, Fadiah Suryani (Foristek, 2023)
Admission of New Students (PPDB) is one of the crucial stages or processes in the world of education, including at the Kindergarten level. A PPDB process that focuses on effective user experience is very important to maintain the reputation of educational institutions and provide a positive experience to parents of prospective students. The Al Qolam IT Kindergarten PPDB process is still carried out manually or conventionally, so it takes quite a long time for parents to process the registration form and return the registration form to the data processing process by the school operator. Considering these problems, designing the PPDB business process with a focus on user experience using BPMN (Business Process Model and Notation), it is hoped that this will create a simpler, more comfortable and intuitive registration experience for parents of prospective students and accuracy in data processing.